Prevalence and Outcomes of Relaparotomy: A Case Series from Tertiary Care Hospital, Mumbai, Maharashtra, India - Chandan Singh; Sahadev Pendurthi; Mansi Mehta; Mukesh Vaktaram Choudhary; Amruta Desai (International Journal of Anatomy Radiology and Surgery)
Relaparotomy is usually performed in certain cases of postoperative complications. Depending on the hospital setting, the incidence of relaparotomy differs. Postoperative care for the patient after the primary surgery also affects the incidence of postoperative sepsis. The purpose of the present study is to identify the indications for relaparotomies so that, in the future, the factors causing these complications can be modified to reduce their incidence. The present study comprises 3,127 primary laparotomies, out of which 135 relaparotomies were performed on 132 patients. The most common age group affected was 31 to 40 years (3.22%), with an average age of 39.25 years. Leakage was the most common indication for relaparotomy, accounting for 77 patients; this includes leaks from anastomosis and perforation. The mean duration between primary laparotomy and relaparotomy was 6.85 days. The mortality rate was 45 (34%) patients. The mean number of days spent in the Intensive Care Unit (ICU) for patients who required continuous monitoring was 4.45 days, while the mean duration of hospitalisation was 26.4 days. Relaparotomy is a lifesaving procedure. The incidence of relaparotomy is influenced by the primary surgical skill, appropriate surgical technique and postoperative infection control. Relaparotomy is most commonly indicated due to leakage from the anastomotic site.